Efficacy of Linaclotide in Reducing Abdominal Symptoms of Bloating, Discomfort, and Pain: A Phase 3B Trial Using a Novel Abdominal Scoring System. (11th September 2021) - Chang, Lin; Lacy, Brian E.; Moshiree, Baha; Kassebaum, Amy; Abel, Jessica L.; Hanlon, Jennifer; Bartolini, Wilmin; Boinpally, Ramesh; Bochenek, Wieslaw; Fox, Susan M.; Mallick, Madhuja; Tripp, Ken; et al.
Abstract : INTRODUCTION: Linaclotide improves abdominal pain and constipation in patients with constipation-predominant irritable bowel syndrome (IBS-C). Patients report additional bothersome abdominal symptoms of bloating and discomfort. The intention of this study was to evaluate linaclotide's efficacy in relieving IBS-C-related abdominal symptoms (bloating, discomfort, and pain) using a novel multi-item Abdominal Score (AS). METHODS: Patients with IBS-C with abdominal pain ≥3 (0–10 scale) were randomized to linaclotide 290 μg or placebo daily for 12 weeks. The AS, derived from the Diary for IBS Symptoms-Constipation, is the average of abdominal bloating, discomfort, and pain at their worst (0 = none, 10 = worst possible). The primary end point was overall change from baseline (CFB) in AS. Secondary end points included CFB in 12-week AS evaluated using cumulative distribution function and 6-week/12-week AS responder (AS improvement ≥2 points for ≥6-week/12-week). RESULTS: Overall, 614 patients (mean age 46.7 years; 81% female) were randomized. All prespecified end points showed significant benefit of linaclotide vs placebo. The mean overall CFB AS reduction for linaclotide was −1.9 vs −1.2 for placebo ( P < 0.0001); the 6-week/12-week AS responder rate was 40.5% for linaclotide vs 23.4% for placebo (odds ratio = 2.2 [95% confidence interval, 1.55–3.12; P < 0.0001]). Diarrhea was the most common treatment-emergent adverse event (linaclotide = 4.6%, placebo = 1.6%). DISCUSSION: Linaclotide significantly reduced multiple abdominal symptoms important to patients with IBS-C (bloating, discomfort, and pain) compared with placebo, as measured by a novel multi-item AS. The AS, derived from the Diary for IBS Symptoms-Constipation, should be considered for use in future IBS-C clinical studies to measure clinically meaningful improvements beyond traditional end points. Abstract :